Insights from an early-stage development mixed methods study on arts-based interventions for older adults following hospitalisation - Amanda M. Clifford; Joanne Shanahan; Hilary Moss; Triona Cleary; Morgan Senter; Erin Marie O'Hagan; Liam Glynn; Desmond O'Neill; Michael Watts; Orfhlaith Ni Bhriain (Elsevier, 2021)
Background: A period of hospitalisation can have negative consequences on physical function and autonomy for older adults, including functional decline, dependency and reduced quality of life. Older adults favour activity that focuses on social connectedness, fun and achievable skills. Objective: The primary aim of this early-stage development mixed methods study was to determine the feasibility and acceptability of a randomised crossover trial design and two arts-based interventions tailored for older adults recently discharged from hospital. Materials and methods: Community-dwelling adults, aged 65 years and older, who reported reduced mobility and less than six weeks post discharge from hospital were invited to participate in the study. Two sites were randomised to either a four-week dance or music therapy intervention, followed by a four-week washout and subsequently to the alternate intervention. Participants and stakeholders were interviewed to share their views and perspectives of the study design and interventions developed. Results: The arts-based interventions were acceptable and safe for participants. Randomisation was completed per protocol and no implementation issues were identified. The outcome measures used were acceptable and feasible for this group of patients and did not lead to fatigue or excessive assessment time. Participants were positive about their experience of the programme. Conclusions: This early development study provides a precursor and several imperative learning points to guide and inform future research in the area. Difficulties in recruitment and attrition were in part due to the barriers encountered when recruiting an incident cohort of vulnerable individuals post hospitalisation.